Value of the HFA‐PEFF and H2FPEF scores in patients with heart failure and preserved ejection fraction caused by cardiac amyloidosis. (15th August 2022) - Tomasoni, Daniela; Aimo, Alberto; Merlo, Marco; Nardi, Matilde; Adamo, Marianna; Bellicini, Maria Giulia; Cani, Dario; Franzini, Maria; Khalil, Anas; Pancaldi, Edoardo; Panichella, Giorgia; Porcari, Aldostefano; et al.
Abstract : Aims: The HFA‐PEFF and H2 FPEF scores have been developed to diagnose heart failure with preserved ejection fraction (HFpEF), and hold prognostic value. Their value in patients with HFpEF caused by cardiac amyloidosis (CA) has never been investigated. Methods and results: We evaluated the diagnostic and prognostic value of the HFA‐PEFF and H2 FPEF scores in 304 patients from three cohorts with HFpEF caused by transthyretin CA ( n = 160, 53%) or immunoglobulin light‐chain CA ( n = 144, 47%). A diagnosis of HFpEF was more likely using the HFA‐PEFF score with 2 (1%), 71 (23%), and 231 (76%) patients ranked as having a low (0–1), intermediate (2–4), or high (5, 6) probability of HFpEF, respectively. Conversely, 36 (12%), 179 (59%) and 89 (29%) of patients ranked as having a low (0–1), intermediate (2–5), or high (6–9) probability of HFpEF using the H2 FPEF score. During a median follow‐up of 19 months (interquartile range 8–40), 132 (43%) patients died. The HFA‐PEFF score, but not the H2 FPEF score, predicted a high risk of all‐cause death which remained significant after adjustment for age, AL‐CA diagnosis, high‐sensitivity troponin T, N‐terminal pro‐B‐type natriuretic peptide, and echocardiographic parameters, including left ventricular global longitudinal strain, left ventricular diastolic function and right ventricular function (hazard ratio 1.51, 95% confidence interval 1.16–1.95, p = 0.002 for every 1‐point increase in HFA‐PEFF). Conclusions: The HFA‐PEFF score has a higher diagnostic utility in HFpEF caused by CA and holds independent prognostic value for all‐cause mortality, while the H2 FPEF score does not. Abstract : The HFA‐PEFF score outperforms the H2 FPEF score as a diagnostic tool in patients with heart failure with preserved ejection fraction (HFpEF) caused by cardiac amyloidosis and holds independent prognostic value for all‐cause mortality, while the H2 FPEF score does not. AL, immunoglobulin light‐chain; ATTR, transthyretin; AUC, area under the curve; CA, cardiac amyloidosis; HR, hazard ratio; ROC, receiver‐operating characteristic.